Improvement in histological endpoints of MAFLD following a 12‐week aerobic exercise intervention. Issue 8 (27th July 2020) - O'Gorman, Philip; Naimimohasses, Sara; Monaghan, Ann; Kennedy, Megan; Melo, Ashanty M.; Ní Fhloinn, Deirdre; Doherty, Derek G.; Beddy, Peter; Finn, Stephen P.; Moore, J. Bernadette; Gormley, John; Norris, Suzanne
Summary: Background: Lifestyle interventions are the primary treatment for metabolic (dysfunction) associated fatty liver disease (MAFLD). However, the histological and cardiometabolic effects of aerobic exercise in MAFLD remain unclear. Aims: To assess the effects of a 12‐week aerobic exercise intervention on histological and cardiometabolic endpoints in MAFLD. Methods: Patients with biopsy‐confirmed MAFLD participated in a 12‐week aerobic exercise intervention. Liver histology, cardiorespiratory fitness (estimated V̇O2max ), physical activity, anthropometry and biochemical markers were assessed at baseline, intervention completion, and 12 and 52 weeks after intervention completion. Results: Twenty‐four patients completed the exercise intervention (exercise group n = 16, control group n = 8). In the exercise group, 12 weeks of aerobic exercise reduced fibrosis and hepatocyte ballooning by one stage in 58% ( P = 0.034) and 67% ( P = 0.020) of patients, with no changes in steatosis ( P = 1.000), lobular inflammation ( P = 0.739) or NAFLD activity score ( P = 0.172). Estimated V̇O2max increased by 17% compared to the control group ( P = 0.027) but this level of improvement was not maintained at 12 or 52 weeks after the intervention. Patients with fibrosis and ballooning improvement increased estimated V̇O2max by 25% ( P = 0.020) and 26% ( P = 0.010), respectively. Anthropometric reductions including body mass ( P = 0.038), waist circumference ( P = 0.015) and fat mass ( P = 0.007) were also observed, but no patient achieved 7%‐10% weight loss. Conclusion: This study highlights the potential benefits of a 12‐week aerobic exercise intervention in improving histological endpoints of MAFLD. The development of strategies to ensure continued engagement in aerobic exercise in MAFLD are needed.